2017
DOI: 10.1097/mpg.0000000000001692
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Infants With Biliary Atresia

Abstract: Objectives: Biliary atresia (BA) occurs in 0.54 of 10.000 of overall live births in the Netherlands. BA has an unfavorable prognosis: <40% of patients are cleared of jaundice after Kasai portoenterostomy (KPE), 4-year transplant-free survival rate is 46% and the 4-year survival rate is ∼75%. Little is known on difficulties in diagnosis and the outcome of BA in preterm infants. We aimed to analyze the incidence and outcome of BA in preterm infants in the Netherlands. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…We analyzed our data from seasonal aspects but could not identify significant time clustering in line with most of the Western and East Asian studies (29); however, this has been controversial as few studies from the United States showed significant clustering of BA from August to October ( 29 ) and December to March ( 14 ). Other demographic characteristics in Saudi Arabia, such as the rate of BASM (10.8%) and prematurity (10.2%), were comparable with the findings of previous studies that showed BASM in 8–14% ( 26 ) and prematurity in 13% ( 30 ). We observed a slight but insignificant female predominance in contrast to most of the Western and East Asian studies that showed significant female predominance ( 16 , 31 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We analyzed our data from seasonal aspects but could not identify significant time clustering in line with most of the Western and East Asian studies (29); however, this has been controversial as few studies from the United States showed significant clustering of BA from August to October ( 29 ) and December to March ( 14 ). Other demographic characteristics in Saudi Arabia, such as the rate of BASM (10.8%) and prematurity (10.2%), were comparable with the findings of previous studies that showed BASM in 8–14% ( 26 ) and prematurity in 13% ( 30 ). We observed a slight but insignificant female predominance in contrast to most of the Western and East Asian studies that showed significant female predominance ( 16 , 31 ).…”
Section: Discussionsupporting
confidence: 88%
“…In our study, of the 53 patients who underwent KPE between the ages of 60 and 90 days, 33% were alive with the native liver at 5 and 10 years. In addition, our data, supported by others ( 30 , 33 36 ), clearly show that undergoing an initial KPE did not impact negatively on the overall LT survival rate. Hence, BA patients presenting between the ages of 60 and 90 days should not be denied KPE.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, some pediatric patients with life-threatening conditions are subject to complex surgical treatments and prolonged anesthetic exposure during the first 3 years of life. 24,[29][30][31][32][33][34] The NHP model has been crucial in describing the risks associated with early life anesthesia in some of the most vulnerable patients.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…The association of prematurity and biliary atresia is, therefore, possible by chance but obviously infrequent. There are three large-scale studies from Sweden [ 18 ], Taiwan [ 19 ] and, most recently, The Netherlands [ 20 ] in which the incidence of BA was reportedly higher in the premature population than in term infants with an odds ratio of 2.9 and 1.65 in the first two studies, respectively. Despite this reported increased incidence, outcomes and characteristics have been rarely reported, consisting largely of case reports (total reported = 5) [ 21 – 23 ].…”
Section: Discussionmentioning
confidence: 99%